Menepis Hoax Media Sosial di Tahun Politik: Pendekatan Systematic Literature Review - Suliyansyah Suliyansyah (Jurnal Adhyasta Pemilu, 2023)
This research aims to delineate strategies to counteract hoaxes during election years, employing a systematic literature review methodology. The review considers articles from journals accredited within the Sinta 1-3 range, focusing on the theme of combating election-related hoaxes, and includes publications from 2019 to September 2022. The study reveals nine pivotal strategies to tackle social media hoaxes during election years, namely: (1) Promoting media literacy and social media ethics. (2) Targeting all societal groups. (3) Implementing preventive actions ubiquitously—at home, in places of worship, workplaces, social gatherings, educational institutions. (4) Engaging in activities fostering critical thinking, such as seminars, discussions, socialization events, community service, collaboration with anti-hoax communities, and other pertinent initiatives. (5) Developing and enhancing courses or materials in schools, universities, and other educational institutions related to media literacy and social media ethics. (6) Proposing development initiatives involving various stakeholders: First, educational and related institutions can design activities encompassing media literacy and social media ethics. Second, parents should be educated to instill media literacy in their children from an early age. (7) Instituting consistent and long-term policies. (8) Implementing regulations and criminal laws that prohibit hoaxes, with penalties for those who violate these rules. (9) Executing vigilant supervision and law enforcement to handle the spread of hoax news and the associated legal penalties.